A Midsummer Night's Dream - Shakespeare, William; Edited By Gill, Roma (New York Oxford University Press, 2009)
Presents the text of Shakespeare's "A Midsummer Night's Dream," a comedy in which two sets of lovers, lost in the woods, get caught up in a dispute between the fairy king and queen, along with a group of local thespians.
Include Illustrations